1981
DOI: 10.1083/jcb.90.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release and ionic changes in the sarcoplasmic reticulum of tetanized muscle: an electron-probe study.

Abstract: Approximately 60-70% of the total fiber calcium was localized in the terminal cisternae (TC) in resting frog muscle as determined by electron-probe analysis of ultrathin cryosections . During a 1 .2 s tetanus, 59% (69 mmol/kg dry TC) of the calcium content of the TC was released, enough to raise total cytoplasmic calcium concentration by -1 mM . This is equivalent to the concentration of binding sites on the calcium-binding proteins (troponin and parvalbumin) in frog muscle . Calcium release was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
223
4

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(248 citation statements)
references
References 92 publications
(181 reference statements)
21
223
4
Order By: Relevance
“…It seems unlikely that the sarcoplasmic reticulum participates in this increase since it appears to gain, not lose, Mg during activity; after a 1.2-s tetanus, the Mg content of the sarcoplasmic reticulum is slightly increased (Somlyo et al, 1981). Mitochondria are also an unlikely candidate since they occupy only 1% of the fiber volume (Mobley and Eisenberg, 1975) and their Mg content is unchanged after a 1.2-s tetanus (Somlyo et al, 1981).…”
Section: The Origin Of the Myoplasmic Mg Transientmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems unlikely that the sarcoplasmic reticulum participates in this increase since it appears to gain, not lose, Mg during activity; after a 1.2-s tetanus, the Mg content of the sarcoplasmic reticulum is slightly increased (Somlyo et al, 1981). Mitochondria are also an unlikely candidate since they occupy only 1% of the fiber volume (Mobley and Eisenberg, 1975) and their Mg content is unchanged after a 1.2-s tetanus (Somlyo et al, 1981).…”
Section: The Origin Of the Myoplasmic Mg Transientmentioning
confidence: 99%
“…4 A shows a transient increase in pH, possibly due to protons entering the sarcoplasmic reticulum accompanying Ca release (Somlyo et al, 1981;Baylor et al, 1982a;. The rise time and duration of the transients are different for the two indicators.…”
Section: Comparison Of the Time Courses Of The Antipyrylazo III Aa(59mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies support the hypothesis that K* ions are the counter-ions for Ca:* fluxes. (i) Electron probe analysis showed that Ca 2* release from the SR during a t,nanus was accompanied by an increase in the concentration of K* ions in the tem linal cisternae [9]. (it) Rapid filtration studies on isolated SR vesicles indicated that the Ca2÷-induced Ca a* release was dependent upon the presence of K + in the release medium and influenced by the K* gradient created across the SR membrane [10].…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of IKur would reduce K + efflux from muscle fibers and cramped myofibers are tetanized 21) . 22) reported that paeoniflorin (a major component of Shakuyaku) and glycyrrhizin depolarized and blocked the neuromuscular junctions.…”
Section: Discussionmentioning
confidence: 99%